AKSIOLOGI PEMIKIRAN PENDIDIKAN ISLAM SYEKH NAWAWI AL-BANTANI DI ERA GLOBALISASI - Irwansyah Suwahyu; Nurhilaliyah Nurhilaliyah; Sitti Muthmainnah (Tadrib: Jurnal Pendidikan Agama Islam, 2020)
This article examines the thoughts of Shaykh Nawawi Al-Bantani in the field of Islamic education in the era of globalization. This study was conducted to explain the importance of Islamic education as a foundation in life through the thinking of one of Indonesia's Islamic scholars. This research is library research in which data is obtained through documents analyzed by content analysis. The results of this study suggest that Islamic Education strongly recommends that its adherents have a strong foundation in religion that will lead it to the right path in this era of globalization. The importance of a balance between mind and soul in facing every life's challenges. In this paper, the main points of view of Syekh Nawawi Al-Bantani on the attitude that Muslims must take towards development and progress in the contemporary context, especially in Indonesia. Because he is an Islamic scholar who greatly contributed to the development of science. This is not wrong, because his works which are numerous and can still be read today by Muslims have added to the knowledge of Islam in particular. This paper uses a library research method, which is research that relies on library materials as a source of information to answer the main ideas of Syekh Nawawi Al-Bantani related to education from an Islamic education perspective. The research stage is to collect relevant materials, then these materials will be read, reviewed, recorded, and then used as best as possible. After all the stages are complete, then the data is analyzed by means of content analysis so that conclusions can be drawn regarding the implementation of Islamic education thought by Syekh Nawawi Al-Bantani in the Era of Globalization.